2016
DOI: 10.1097/sla.0000000000001374
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Intraportal Chemotherapy Combined With Adjuvant Chemotherapy (mFOLFOX6) for Stage II and III Colon Cancer

Abstract: Combination of intraoperative intraportal chemotherapy with mFOLFOX6 reduced the occurrence of distant metastases and improved disease-free survival in patients with stage II and stage III colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…It has been reported that peri-operative intra-portal chemotherapy combined with adjuvant chemotherapy prolonged disease-free survival after primary tumor resection and decreased liver metastasis for stage II and III colon cancer patients, without liver metastasis [39]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that peri-operative intra-portal chemotherapy combined with adjuvant chemotherapy prolonged disease-free survival after primary tumor resection and decreased liver metastasis for stage II and III colon cancer patients, without liver metastasis [39]. …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that 5-FU administered directly into the portal vein adjuvantly may decrease distant metastases [37, 38]. Chang, et al [39] reported that peri-operative intraportal (iPV) chemotherapy combined with adjuvant chemotherapy was useful to prolong disease-free survival after primary tumor resection and decreased liver metastasis for stage II and III colon-cancer patients without liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, only in Europe, >370,000 people suffered from it, and ~200,000 people succumbed to the disease, which accounted for 12% of all cancer mortalities (2). In China, at present, colon cancer is ranked as the fifth most common tumor, whose growth speed is very fast, particularly in certain large cities (3). However, colon cancer's lack of specificity in terms of clinical symptoms leads to patients being often misdiagnosed, thus delaying treatment (4).…”
Section: Introductionmentioning
confidence: 99%
“…Adding oxaliplatin to FU has resulted in an approximate 20% relative risk reduction for disease-free survival. At present, the first line treatment of colorectal cancer includes mFOLFOX6 with or without targeted drugs bevacizumab or cetuximab [2, 3]. The mFOLFOX6 regimen contains leucovorin calcium (folinic acid), fluorouracil, and oxaliplatin.…”
Section: Introductionmentioning
confidence: 99%